Theory of fluorescence polarization in magnetically oriented photosynthetic systems. - Knox, R S (1978)
Many cells and cell fragments are known to assume specific alignments with respect to an applied magnetic field. One indicator of this alignment is a difference between the intensities of fluorescence observed in polarizations parallel and perpendicular to the magnetic filed. We calculate these two intensities using a model that assumes axially symmetric membranes and that covers a wide variety of shapes from flat disk to right cylinder. The fluorescence is assumed to originate at chromophores randomly exicted but nonrandomly oriented in the membranes. The membrane alignment is assumed to be due to the net torque on a nonrandom distribution of diamagnetically anisotropic molecules. The predicted results are consistent with most magnetoorientation data from green cells, but we are able to show that Chlorella data are not consistent with the hypothesis that the membranes have, and maintain, a cuplike configuration.